PENGUNGKAPAN SDGs PADA LAPORAN KEBERLANJUTAN PT PETROKIMIA GRESIK BERDASARKAN STANDAR GLOBAL REPORTING INITIATIVE (GRI) PERIODE 2018-2020 - Amiroh Nur Amaliyah; Wuryan Andayani (TEMA, 2022)
This study aims to disclose the sustainability performance reporting of PT Petrokimia Gresik in 2018-2020 contributing to the SDG program achievement, and to disclose the sustainability performance reporting based on 2016 Global Reporting Initiative (GRI) Standards. This study employs qualitative case study approach and includes secondary data of PT Petrokimia Gresik's 2018-2020 sustainability report accessible from the company's official website. In analyzing the problem, this study utilizes content analysis to thoroughly disclose the sustainability report. The results of this study revealed that the sustainability performance of PT Petrokimia Gresik contributing to the SDG achievement changed annually indicating 31.95%, 31.36%, 33.73% from 2018 to 2020 respectively. Based on the 2016 GRI Standards, the 2018 and 2019 disclosure percentages of PT Petrokimia Gresik were included in Partially-Applied category representing 75.91% and 75.30%, respectively, whilst, in 2020 the disclosure reached 90,89%, making it included in the Well-Applied category.